Perancangan Sistem untuk Minimasi Limbah B3 di PT. XYZ Menggunakan Pendekatan SSM (Soft System Methodology) - Sukarlina, Nina; Sriwana, Iphov Kumala (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2022)
PT. XYZ is a company that produces pharmaceutical products for livestock. Most of the raw materials for veterinary drugs consist of B3 powder (toxic and hazardous materials). Waste from the production process is unavoidable, one of the types of waste produced by PT. XYZ is B3 powder wastes. According to the Environmental Service (DLH) B3 waste cannot be directly discharged into the environment, therefore PT. XYZ uses 3rd party services in processing B3 waste disposal. PT. XYZ produces powdered B3 waste at an average of 267.12 kg/month, the cost that must be incurred by the company to manage B3 waste and the value of loss of raw materials is Rp. 28,094,703.70/year. This study aims to design a system for the minimization of B3 waste by using a Soft System Methodology (SSM) approach. The proposed changes from this research use the 3R principle (reduce, reuse, recycle). The implementation of the proposed changes can result in cost efficiency incurred by the company for B3 waste management of Rp. 18,368,995.87/year.